Assessment of planktonic metabolism in the artic and subtropical oceans by the 18O method - Mesa Cano, Elena (Universidad de Granada, 2017)
The metabolism of oceanic phytoplankton, consisting of gross primary production (GPP) and respiration (R), regulates biogeochemical cycles and climate. Plankton photosynthesis is responsible for half of the world primary production and fuels the marine food web and the biological CO2 pump, which makes oceanic phytoplankton primary production a fundamental process at the global scale. However, there is a current debate over the estimations coming from different methods to assess GPP. The 18O method is the most accurate one and the only one that measures GPP directly, but has been used in very few studies (less than twenty, to the best of our knowledge) which are not representative of the global ocean. The other metabolic process, plankton respiration, is a major component of global CO2 production. At the ecosystem level, respiration integrates so many aspects of the functioning, that long-term shifts in respiration may provide the best warning system for global change. However, global respiration data are much more scarce than primary production data, there are around 20,000 estimates of oceanic production for each estimate of respiration rate. In addition, respiration is usually measured in dark conditions, assuming that it is equivalent to respiration in the light, which has not been proved and might thus be biasing global models of gas fluxes. The main aim of this PhD thesis is to go a step further in the global assessment of planktonic metabolism, by evaluating GPP18O (i.e. GPP measured with the 18O method) in the Arctic and in the tropical and subtropical ocean, and by testing the hypothesis of equal respiration in the dark and in the light. We assessed GPP18O in the context of three different studies: in the tropical and subtropical ocean (Malaspina Expedition); in the European Arctic Sector (to the west of Svalbard islands); and in a fjord in the east coast of Greenland (Young Sound). We evaluated GPP18O in 84 stations across the Atlantic, Pacific and Indian Oceans, in the framework of the 2010 Malaspina ...